Investigation of steel wire mechanical behavior and collaborative mechanism under high temperature. (January 2022) - Sun, Guojun; Li, Zhihao; Wu, Jinzhi; Ren, Jingying
Abstract: This study investigated the high-temperature mechanical properties and collaborative working mechanism of zinc-5% aluminum-mixed mischmetal alloy-coated steel strand cables (M-C cables) and internal steel wires by numerical analysis, based on the experimental data for the high-temperature mechanical properties of steel wire. The high-temperature mechanical properties of zinc-5% aluminum-mixed mischmetal alloy-coated steel (M-C steel) with round and Z-shape cross-section shapes were studied in the temperature range of 30–800 °C using the constant temperature loading test method. The two-stage Ramberg-Osgood model for M-C steel wires at elevated temperatures is proposed for modeling of the M-C steel wires. Furthermore, the equations for the reduction in the nominal yield strength, elastic modulus and ultimate strength for M-C steel wires at elevated temperatures are proposed. Numerical analysis and investigation of the high-temperature mechanical properties of normal M-C cables and locked M-C cables under eight temperature conditions are carried out. Based on the high-temperature constitutive relationship of the round and Z-shaped M-C steel wires obtained experimentally, the thermostatic drawing process is simulated at different temperatures for two types of M-C cables. The high-temperature stress-strain relationship between the two and the relevant high-temperature mechanical performance index were obtained. According to the numerical simulation results, the energy, contact stress distribution and radial displacement deformation of M-C cables under the different temperature condition were evaluated and analyzed. The collaborative working mechanism of M-C cabled affected by temperature was revealed. Graphical abstract: Unlabelled Image Highlights: The equations for the degradation of yield strength, elastic modulus and ultimate strength of round and Z-shape M-C steel wires at high temperature were determined. Finite element models accurately simulate the stress-strain behaviors of the cables at elevated temperatures. The collaborative working mechanism for M-C cables and internal steel wires was investigated.